EXPERIMENTS ON NORMAL AND IMMUNE MICE WITH A BACILLUS OF MOUSE TYPHOID - Webster, Leslie T. (The Rockefeller University Press, 1922)
If live cultures of a mouse strain of Bacillus pestis caviæ are injected intrapleurally or intraperitoneally into normal mice, there occurs an initial lag in the rate of bacterial multiplication lasting a few hours, followed by a rapid and continued acceleration of growth until the death of the animal. If live cultures of this organism are given per os to normal mice, there occurs an incubation period of 5 to 6 days, after which the animal usually develops symptoms of disease and succumbs. A small percentage of mice, however, proves refractory to infection by this route. If live cultures of this organism are injected intrapleurally or intraperitoneally into mice previously "vaccinated" intrapleurally or intraperitoneally, they are partially destroyed and held in check by the protective mechanisms of the animal body for 2 or 3 days. Subsequently the rate of bacterial multiplication increases gradually until the death of the animal. The partial protection following this type of "vaccination" is entirely of a general nature; no evidence of a local immunity has been obtained. Mice given one, two, or three subcutaneous doses of "vaccine" show a similar relative increase in resistance to the subsequent intraperitoneal or per os injection of live organisms. Feeding mice live or killed cultures of this organism induces a definite protection against subsequent intrastomachal and intraperitoneal injections of live organisms. The immunity developed in this way is also of a general as opposed to a local nature.